Hypodermoclysis for Correction of Hyperosmolar Dehydration and Severe Electrolyte Disturbances: A Case Report - Marco Túlio Gualberto Cintra (Brazilian Society of Geriatrics and Gerontology, 2024)
The treatment of dehydration and severe electrolyte disturbances using hypodermoclysis is usually contraindicated, but the level of evidence for its recommendation is based on expert opinion. This case report describes an older patient receiving palliative care who developed hyperosmolar dehydration with severe hypernatremia, acute kidney injury, and hyperkalemia. She was treated with hypodermoclysis using a hypotonic solution, which led to complete resolution of the condition. In conclusion, further studies on the use of hypodermoclysis for the treatment of severe hydroelectrolytic disorders are needed.